MODERNIZATION AND COMMERCIALIZATION OF RELIGIOUS TOURISM ON REDUCTION OF PIWULANG VALUES SUNAN DRAJAT LAMONGAN (CRITICAL STUDY OF THE WEAKENING OF THE TEACHINGS AND CULTURAL VALUES OF SUNAN DRAJAT LAMONGAN) - Miftachul Ulum (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2019)
Calling Sunan Drajat already familiar and his work has resonated in the archipelago. The struggle and character of the Walisongo to date remain in the hearts of the Indonesian people so that it becomes a separate tradition to always be blessed through the moment of Walisongo pilgrimage. The community is so hypnotized by the power to always appreciate good intentions through Walisongo pilgrimage moments as a form of gratitude and want to imitate Kipra and Walisongo's struggle. But with the development of the times and advances in technology, the community has been hypnotized by the presence of pilgrims. The community has used and tried to make profits only regardless of the actual conditions that religious tourism has become a magnet for mere profit. Many are forgotten and neglected from the essence of the sunan Drajat Lamongan tomb, which is a place to get closer to Allah on a pilgrimage.